THE EFFECT OF PERCEIVED ORGANIZATIONAL SUPPORT AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE THROUGH EMPLOYEE ENGAGEMENT PT. DUWA ADMIMUDA - Shiffany, Siti Hasna; Soegiarto, Dwi; Fahira, Keke Tamara (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2025)
This research aims to analyze the influence of perceived organizational support and organizational culture on employee performance through Employee Engagement. This research is quantitative research using data collection methods in the form of distributing questionnaires. This research used a sample of 167 respondents. The data analysis technique for this research uses Structural Equation Modeling (SEM) AMOS V.24. The results of this research show that perceived organizational support has a positive and insignificant effect on employee performance, organizational culture has a positive and significant effect on employee performance, perceived organizational support has a negative and insignificant effect on employee engagement, organizational culture has a positive and significant effect on employee engagement. , employee engagement has a positive and significant effect on employee performance, employee engagement is not able to mediate the effect of perceived organizational support on employee performance, and employee engagement is not able to mediate the effect of organizational culture on employee performance.